(untitled) (Ghana Journal of Science, Technology and Development, 2020)
Taenia solium cysticercosis is a cosmopolitan foodborne disease that is neglected in many endemic tropical societies. The disease situation is less understood in parts of sub-Saharan Africa including Ghana, meanwhile useful surveillance data are needed from all endemic localities for designing effective intervention strategies. The present study estimated abattoir-based prevalence and distribution of T. solium cysticercosis in pigs from northern Ghana. A survey was carried out at the Kumasi abattoir to screen for cyst infection and localization sites, and evaluate the handling of infected carcasses. Taenia solium cysticercosis infection was noted in pigs at the abattoir, drawn from all five Regions of northern Ghana. Generally, porcine cysticercosis had 9.73% prevalence across the Regions with the Upper East Region (10.10%) being noted as a key focus of the cestode. Animals from the Upper West, Savannah, Northern and North East Regions also recorded a prevalence range of 8.25 – 12.12%. The results indicate considerable prevalence of T. solium cysticercosis that was in wide distribution in pig in northern Ghana and point to a public health threat in cities where such infected pigs are slaughtered.